Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To solve the system of equations:
[tex]\[ \begin{array}{l} \frac{7}{3} x + y = 0.4 \\ 0.6 x - y = 3 \end{array} \][/tex]
we follow these steps:
1. Rewrite the equations for better visualization:
Equation 1: \(\frac{7}{3} x + y = 0.4\)
Equation 2: \(0.6 x - y = 3\)
2. Isolate \(y\) in Equation 2:
[tex]\[ y = 0.6 x - 3 \][/tex]
3. Substitute \(y\) from Equation 2 into Equation 1:
[tex]\[ \frac{7}{3} x + (0.6 x - 3) = 0.4 \][/tex]
4. Combine like terms and simplify:
[tex]\[ \frac{7}{3} x + 0.6 x - 3 = 0.4 \][/tex]
Convert \(0.6 x\) to a fraction to combine with \(\frac{7}{3} x\):
[tex]\[ \frac{7}{3} x + \frac{6}{10} x - 3 = 0.4 \][/tex]
Simplify \(\frac{6}{10}\) to \(\frac{3}{5}\):
[tex]\[ \frac{7}{3} x + \frac{3}{5} x - 3 = 0.4 \][/tex]
Find a common denominator for the fractions:
[tex]\[ \frac{35}{15} x + \frac{9}{15} x - 3 = 0.4 \][/tex]
Combine the fractions:
[tex]\[ \frac{44}{15} x - 3 = 0.4 \][/tex]
5. Solve for \(x\):
Add 3 to both sides:
[tex]\[ \frac{44}{15} x = 3.4 \][/tex]
Multiply both sides by \(\frac{15}{44}\):
[tex]\[ x = \frac{3.4 \times 15}{44} \][/tex]
Simplify:
[tex]\[ x \approx 1.159 \][/tex]
6. Substitute \(x\) back into Equation 2 to find \(y\):
[tex]\[ y = 0.6 (1.159) - 3 \][/tex]
Calculate:
[tex]\[ y \approx 0.6954 - 3 \][/tex]
So:
[tex]\[ y \approx -2.305 \][/tex]
Therefore, the solution to the system of equations is:
[tex]\(\boxed{(1.159, -2.305)}\)[/tex]
[tex]\[ \begin{array}{l} \frac{7}{3} x + y = 0.4 \\ 0.6 x - y = 3 \end{array} \][/tex]
we follow these steps:
1. Rewrite the equations for better visualization:
Equation 1: \(\frac{7}{3} x + y = 0.4\)
Equation 2: \(0.6 x - y = 3\)
2. Isolate \(y\) in Equation 2:
[tex]\[ y = 0.6 x - 3 \][/tex]
3. Substitute \(y\) from Equation 2 into Equation 1:
[tex]\[ \frac{7}{3} x + (0.6 x - 3) = 0.4 \][/tex]
4. Combine like terms and simplify:
[tex]\[ \frac{7}{3} x + 0.6 x - 3 = 0.4 \][/tex]
Convert \(0.6 x\) to a fraction to combine with \(\frac{7}{3} x\):
[tex]\[ \frac{7}{3} x + \frac{6}{10} x - 3 = 0.4 \][/tex]
Simplify \(\frac{6}{10}\) to \(\frac{3}{5}\):
[tex]\[ \frac{7}{3} x + \frac{3}{5} x - 3 = 0.4 \][/tex]
Find a common denominator for the fractions:
[tex]\[ \frac{35}{15} x + \frac{9}{15} x - 3 = 0.4 \][/tex]
Combine the fractions:
[tex]\[ \frac{44}{15} x - 3 = 0.4 \][/tex]
5. Solve for \(x\):
Add 3 to both sides:
[tex]\[ \frac{44}{15} x = 3.4 \][/tex]
Multiply both sides by \(\frac{15}{44}\):
[tex]\[ x = \frac{3.4 \times 15}{44} \][/tex]
Simplify:
[tex]\[ x \approx 1.159 \][/tex]
6. Substitute \(x\) back into Equation 2 to find \(y\):
[tex]\[ y = 0.6 (1.159) - 3 \][/tex]
Calculate:
[tex]\[ y \approx 0.6954 - 3 \][/tex]
So:
[tex]\[ y \approx -2.305 \][/tex]
Therefore, the solution to the system of equations is:
[tex]\(\boxed{(1.159, -2.305)}\)[/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.